Mercury removal using pseudomonas putida (Attc : 49128) - Khorsiah, Sabar (2008)
Microbes have been used to solve environmental problems for many years. The use microorganism to sequester, precipitate or alter the oxidation state of various heavy metals has been extensively studied. Processes by which microorganism interacts with toxic metal are very diverse. The objective of this research is to remove the mercury using Pseudomonas putida.In this research, Pseudomonas putida strain, a mercury resistant bacterium, which is able to reduce ionic mercury to metallic mercury, was studied.This study has been carried out using mercury nitrate in the concentration 1-5ppm. In this study the P.putida must observed first to know the best condition that can remove mercury with effectively. Maximum removal capacity for bacterium was found to be 80%.Thus; bacterial removal of mercury is a potential biological treatment for mercury environmental pollutants. -Author